Ectomycorrhizal fungi induce systemic resistance against insects on a nonmycorrhizal plant in a CERK1‐dependent manner. Issue 2 (8th July 2020) - Vishwanathan, Kishore; Zienkiewicz, Krzysztof; Liu, Yang; Janz, Dennis; Feussner, Ivo; Polle, Andrea; Haney, Cara H.
Summary: Below‐ground microbes can induce systemic resistance against foliar pests and pathogens on diverse plant hosts. The prevalence of induced systemic resistance (ISR) among plant‐microbe‐pest systems raises the question of host specificity in microbial induction of ISR. To test whether ISR is limited by plant host range, we tested the ISR‐inducing ectomycorrhizal fungus Laccaria bicolor on the nonmycorrhizal plant Arabidopsis thaliana . We used the cabbage looper Trichoplusia ni and bacterial pathogen Pseudomonas syringae pv. tomato DC3000 ( Pto ) as readouts for ISR on Arabidopsis . We found that root inoculation with L. bicolor triggered ISR against T. ni and induced systemic susceptibility (ISS) against the bacterial pathogen Pto . We found that L. bicolor‐ triggered ISR against T. ni was dependent on jasmonic acid signaling and salicylic acid biosynthesis and signaling. Heat‐killed L. bicolor and chitin were sufficient to trigger ISR against T. ni and ISS against Pto . The chitin receptor CERK1 was necessary for L. bicolor‐ mediated effects on systemic immunity. Collectively our findings suggest that some ISR responses might not require intimate symbiotic association, but rather might be the result of root perception of conserved microbial signals.